HUBUNGAN LAMA MENDERITA DAN KOMPLIKASI DENGAN KUALITAS TIDUR PASIEN DIABETES MELLITUS DI RS DR. M HAULUSSY AMBON - Syulce Luselya Tubalawony; Nenny Parinussa (Jurnal Ilmiah Global Education, 2023)
Diabetes mellitus is a serious threat to global health. According to the World Health Organization in 2016 stated that 70% of all world deaths and more than half of the disease burden. The longer the patient has DM with increased blood glucose levels, the higher the possibility of complications occurring and the effect on disturbing the patient's sleep pattern. The purpose of this study was to determine the relationship between the duration of suffering from DM and complications of DM on the sleep quality of DM sufferers at Dr M Haulussy Hospital, Ambon. This is an analytical study with a cross sectional approach. The population in this study were 52 outpatients at the internal medicine polyclinic at Dr M Haulussy Ambon Hospital and the sampling technique was total sampling. The research instrument uses a questionnaire. The results showed that there was a relationship between duration of DM and sleep quality in DM patients with a p value of 0.014 <0.05 and there was a relationship between DM complications and sleep quality in DM patients with a p value of 0.009 <0.05. Based on this research, it is hoped that it can be input for health workers, especially nurses, to prevent complications of DM so that the patient's sleep quality is also good.